2014
DOI: 10.1093/eurheartj/sut014
|View full text |Cite
|
Sign up to set email alerts
|

Management of heart failure complicating acute coronary syndromes in Montenegro and Serbia

Abstract: Montenegro and Serbia with a diagnosis of ACS during the period between October 2012 and August 2013. Among 1115 patients, 94 (8.4%) had an admission diagnosis of HF (Killip Class II or III). Heart failure patients were significantly older (P , 0.001). Heart failure was more frequently associated with hypertension. When compared with patients presenting without HF (Killip Class I), those with HF had lower rates of reperfusion therapy either by percutaneous coronary intervention (47.9 vs. 60.7%, P ¼ 0.015) or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…It was found in one study that Survival is higher in patients without congestive heart failure than with congestive heart failure patients. 9,10 Ahit MC, et al reported the 10.6% frequency of HF in NSTEMI patients with old age, female gender, very high heart rate, higher presenting heart rate, diabetes, hypertension and previous history of MI are significant risk factors noted. 11,12 Kaul P, et al reported 13.6% patient of HF in STEMI and 14.8% patients of HF with NSTEMI (P < .01).…”
Section: Introductionmentioning
confidence: 99%
“…It was found in one study that Survival is higher in patients without congestive heart failure than with congestive heart failure patients. 9,10 Ahit MC, et al reported the 10.6% frequency of HF in NSTEMI patients with old age, female gender, very high heart rate, higher presenting heart rate, diabetes, hypertension and previous history of MI are significant risk factors noted. 11,12 Kaul P, et al reported 13.6% patient of HF in STEMI and 14.8% patients of HF with NSTEMI (P < .01).…”
Section: Introductionmentioning
confidence: 99%